Studi meta analisis: Small effect size pada korelasi antara dukungan sosial dan penyesuaian diri - Dedi Nasruddin; Ananta Yudiarso (University of Muhammadiyah Malang, 2022)
The purpose of this study was to statistically test the effect size correlation between social support and adjustment using meta-analysis. This study uses a meta-analysis of literature reviews of 16 international research journals. The total of participants was 4,475. Researchers followed the guidelines from PRISMA and MARS. Using statistical analysis of effect size correlation (r-value and sample size) (N), We found a small effect size correlation. The effect size value obtained from the random effect r = 0.149 (CI = -0.006 to 0.304), I² (inconsistency) = 96.29%. Our findings indicated that social support and adjustment had a direct small effect size.